2021
DOI: 10.30865/mib.v5i2.2924
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peneriman Sistem Ujian CBT Menggunakan Metode UTAUT (Unified Theory of Acceptance and Use of Technology) di Lingkungan Kampus

Abstract: Information system technology has been applied to all organizations, both organizations and non-profits, even though the development of information technology has been felt by the education sector. Slowly technology began to replace some of the work and activities carried out by humans. However, today's technology is still not perfectly applied. This study tries to get an idea of how the participants respond using computer technology in carrying out their exam process or better known as the Computer Based Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Students' intention to use e-learning will increase if it is required for learning activities [26]. The results of other studies conducted by [1], [3], [15], [31] on the acceptance of online exam systems also found that SI has a positive influence on BI.…”
Section: ) Effect Of Si On Bimentioning
confidence: 83%
See 1 more Smart Citation
“…Students' intention to use e-learning will increase if it is required for learning activities [26]. The results of other studies conducted by [1], [3], [15], [31] on the acceptance of online exam systems also found that SI has a positive influence on BI.…”
Section: ) Effect Of Si On Bimentioning
confidence: 83%
“…Then, regarding the acceptance of web services, students can complete academic activities correctly and quickly, thus having a positive impact on studies and improving academic performance [20]. Research results [1], [15], [31] on accepting online exam systems also found that PE has a positive and significant influence on BI.…”
Section: ) Effect Of Pe On Bimentioning
confidence: 99%
“…Pengujian validitas dengan convergen validity akan diihat berdasarkan pada nilai loading factor serta average variance extracted (AVE) didapatkan. Indikator dan variabel dapat dikatakan valid apabila loading factor-nya lebih besar dari 0,7, kemudian nilai AVE yang dihasilkan lebih besar dari 0,5 [15]. Hasil dari loading factor pada indikator penelitian ditemukan pada tabel 4 yang terletak di bawah.…”
Section: Convergen Validityunclassified
“…Untuk menguji validitas menggunakan discriminant validity, akan diperiksa nilai cross loading dan fornell lacker's. Nilai cross loading dan fornell lacker's yang hasilnya lebih dari 0,7 dan lebih besar dibandingkan nilai dari korelasi antar variabel laten, berturut-turut, menandakan indikator dan variabel penelitian telah valid [15]. Tabel 6 di bawah ini menunjukkan nilai cross loading untuk indikator yang digunakan.…”
Section: Discriminant Validityunclassified
“…Kata Kunci -SMART-PLS, TAM, UTAUT I. PENDAHULUAN Perkembangan teknolgi informasi dan komunikasi menghasilkan perubahan cukup besar bagi kehidupan manusia. Dengan berkembang pesatnya teknologi khususnya dalam pendidikan memudahkan individu dalam melakukan aktivitias akademik secara online [1]. Dalam memaksimalkan aktivitas suatu instansi khususnya pada Perguruan Tinggi sangat dibutuhkannya sistem informasi yang mampu menyajikan informasi secara efektif dan efisien dan sistem tersebut bernama sistem informasi akademik [2].…”
unclassified